Impact of demographic factors and leadership style on employees’ Job satisfaction (2014)
This study investigated the impact of leadership style and demographic variables on employees’ job satisfaction in four selected telecommunication companies in Lagos, Nigeria. The study adopted a cross-sectional survey design in which 227 participants were accidentally sampled from a employee population of 1174. Participants comprised of 102 males and 125 females aged between 19 and 59 years with mean age of 33.82 and standard deviation of 8.12. Primary data were generated through structured questionnaire administered on respondents to examine the influence of leadership style on employees’ job satisfaction. Three hypotheses were generated and tested. Results showed that there was a significant positive relationship between democratic or employee-centered leadership style and general job satisfaction among employees (r=.22). Demographic variables (marital status, gender, work experience and age) jointly predicted general job satisfaction among employees in the telecommunication companies {R=.334; R²=.112; F(4,222)=6.984; p<.05}. It was revealed that gender had significant influence on general job satisfaction among employees in the telecommunication companies [t (225) =3.575; P<.05]. The study concluded that democratic leadership style is a positive correlate of employee job satisfaction in the telecommunication companies. Also, some demographic variables determine employee job satisfaction. It was recommended that organizations and managers should be mindful of, and improve on, the leadership styles they adopt. Organizations should also consider employees first in management decisions to enhance satisfaction among employees because a satisfied worker is a productive employee and an asset to the organization. Several implications of findings were discussed